We honestly can look after your dog - Child, Lauren (London : Puffin, 2006)
Lola and Lotta convince Charlie's friend Marv that they can look after his dog Sizzles while they are all at the park, but the girls actually know less about dogs than they think they do.
"Text based on script written by Bridget Hurst and Carol Noble"--T.p. verso.
2.1
K-3
Keywords: Brothers and sisters -- Juvenile fiction; Dogs -- Juvenile fiction; Brothers and sisters -- Fiction; Dogs -- Fiction; Dogs -- Fiction; Siblings -- Fiction